Removal of a Penile Constriction Device with a Large Orthopedic Pin Cutter - Avinash Chennamsetty; David Wenzler; Melissa Fischer (Case Reports in Urology)
Penile strangulation is an infrequent clinical condition that has widely been reported. It usually results following placement of a constriction device to enhance sexual stimulation. Early treatment is essential to avoid potential complications, including ischemic necrosis and autoamputation. We describe the use of a Large Orthopedic Pin Cutter to remove a metal penile constriction device in the Emergency Department (ED). This case report describes the relatively safe technique of using an instrument available in many hospitals that can be added to the physician’s arsenal in the removal of metal constriction devices.